Spiritual Assessment Scale Psychometric Testing - Faudziah Yusof; Nor Ba’yah Abdul Kadir; Siti Marziah Zakaria; Normaliza Ab Malik (Human Resource Management Academic Research Society, 2024)
Vol. 13, No. 6, 2023, Pg. 1685 – 1696